Food Security Challenges and Approaches - Haseeb Ahmad, Muhammad; Imran, Muhammad; Kamran Khan, Muhammad (Sustainable Development, 2023)
Food security and accessibility are being threatened by climate change, inadequate agricultural practices, and poor post-harvest techniques, among other factors. This book discusses sustainable approaches that can be utilized to ensure food security, such as fortification of bioactive components, genetic modification of food, and utilization of insects as food. It also describes practices to improve agricultural productivity and discusses the impact of natural disasters on food security.